Non-consensus investing : being right when everyone else is wrong - Bhansali, Rupal J. (Columbia Business School Publishing : Columbia University Press, 2019)
"The book aims to share investment principles that have enabled the author, a successful money manager, to deliver superior risk adjusted returns throughout her 25 year career - spanning markets both bull and bear, domestic and international, developed and emerging and across market cap ranges. Active Investing has developed an inferior track record and poor reputation, not because it is not possible to beat the market but because a whole generation of investment professionals have failed to understand what it takes to succeed in the asymmetric sport of investing - where it is not enough to be correct, one also has to be non-consensus. The author calls her approach Non-Consensus Investing (NCI), distinguished from standard value investing by its emphasis on on what you get - the future risk, returns and growth of the business, rather than on what you pay. In other words, following the NCI approach, an investor is first a business analyst, second a financial analyst, and lastly a securities analyst. While traditional value investing is increasingly outsourced to computers because of its focus on strictly quantitative analysis, NCI relies on real-world heuristic frameworks. Bhansali outlines ten of the principles that she has followed throughout her successful career, one per chapter, with examples to show both the merits and pitfalls of her approach"--Provided by publisher